Idioms Translation Strategies in Surah Yasin English Version - Hariyanto Hariyanto (Jurnal Ilman: Jurnal Ilmu Manajemen, 2020)
the research deals with idioms translation strategies. The aim of this study were to describe the translation strategies in Surah Yasin English version. The research was conducted by using qualitative design. The data of this study were words, phrases and clause. The data were collected through documentary technique and the instrument was the documentary sheet. The data were analyzed by using Miles and Huberman’s Interactive Model. The result of this study revealed that: (1) The types of idioms translation strategies in Surah Yasin English version found by the researcher namely (a) idiom of similar meaning aand form, (b) idiom of similar meaning but dissimilar form, (c) translation by paraphrase, (d) word for word strategy. The translator wanted the English translated version of Surah Yasin English Version easy to understand by the global reader. This translation was aimed to the acceptance of target reader